Regulating Mg / Fe interfacial compound formation by in-situ alloying with Gd and Y - Qiang Lang; Nan Li; Xin Liu; Muhammad Shehryar Khan; Gang Song; Liming Liu (Journal of Magnesium and Alloys)
This study revealed that the presence of Cr and Ni in stainless steel is one of the leading causes for the weakening of the Mg / Fe interface when using a traditional Mg-Zn-Al (i.e., AZ61) filler wire. By using a novel Mg-Gd-Y-Zr filler wire without Al, the interfacial structure between Mg / Fe was optimized, and the joint integrity was significantly improved. Using advanced multiscale characterization tools, the coherent matching mechanism of rare earth elements in regulating Mg / Fe interfacial compounds was clarified. The results showed that Gd and Y exhibited lower diffusion activation energy and faster diffusion rates in Fe compared to Al resulting in IMCs with more stiffness and mechanical integrity than Al-Mg compounds that are generated at the Mg / Fe interface when using the AZ61 filler wire. High-resolution TEM results revealed that the lattice distortion caused by the diffusion of metal elements changes the original semi-coherent matching interfaces of (0 0 0 1)HCP−Mg and (0 1 2)BCC−Mg24(Y, Gd)5, as well as lattice planes of (0 1 2)BCC−Mg24(Y, Gd)5 and (57¯ 2 3)HCP-Fe17(Y, Gd)2 into a coherent matching interface, which is known to improve mechanical strength. Although lattice planes of (57¯ 2 3)HCP-Fe17(Y, Gd)2 and (1 1 1)BCC-Fe were found to be incoherent interfaces, it was found that Gd, Y, and Zr with larger atomic radii compared to Al diffused into the bulk Fe to form a wide range of (Fe, Gd, Y, Zr, Cr, Ni, Mn) interstitial solid solutions, which helped strengthen the integrity of the joint. The results showed that the load bearing capacity of the AZ31B / Mg-RE / 316 L joint was about 290 N/mm, which is 2.5 times that of the AZ31B / AZ61 / 316 L joints, which was measured at 115 N/mm.